Integration of Local Medicinal Plant Potential Ethnobotany in Primary Schools as a Strategy for Strengthening Character Education and Health Literacy - Dewi Robiatun Muharomah; Maya Rahayu (Postgraduate, University of Mataram, 2025)
This study aims to integrate the potential of local medicinal plants based on ethnobotany into primary school learning as a strategy to strengthen character education and health literacy. The research employed a Mixed-Methods Sequential Exploratory (MMSE) design, beginning with a qualitative phase through interviews and observations with local communities around Mount Karang, Pandeglang. The qualitative exploration identified 15 species of local medicinal plants that are still commonly used, both for daily health needs and as part of cultural heritage. These findings were then operationalised into test items and questionnaires, which were subsequently administered in the quantitative phase to 43 primary school students. The results demonstrated a significant improvement after the integration of ethnobotanical content in learning. Students’ understanding of medicinal plants increased from 45% to 80%, environmental care attitude from 50% to 85%, responsibility from 60% to 88.7%, and the application of healthy living from 48% to 84%. These findings indicate that integrating local medicinal plants into the curriculum not only enhances students' health literacy but also fosters values of care and responsibility rooted in local wisdom. In conclusion, this research highlights that ethnobotany-based learning can serve as an effective strategy to nurture healthy, responsible, and culturally grounded young generations in primary schools